Eksplorasi konsep matematika dalam budaya mindang tradisional di desa Jerukwangi Jepara Jawa Tengah: Studi etnomatematika - Rohman, Muhammad Ainur; Widiyastuti, Wahyuning (Universitas PGRI Semarang, 2024)
This research was conducted to determine the representation of mathematical concepts integrated with the traditional home mindang process. The research method is descriptive qualitative with an ethnographic approach. Based on the findings from the analysis of a series of mindang processes, patterns were found that represent mathematical concepts namely statistics: mean, measurement of time, mass, liters, length, and temperature, geometry on the flat plane: square, vector, geometry on the spatial plane: beam, tube, and triangular prism, and geometry of transformation: rotation. The results can be used to design more meaningful learning based on Contextual Teaching and Learning (CTL).